2008
DOI: 10.1002/hyp.7091
|View full text |Cite
|
Sign up to set email alerts
|

Mercury transport in response to storm events from a northern forest landscape

Abstract: Abstract:Concentrations and fluxes of mercury (Hg) species in surface waters of forested watersheds are affected by hydrological events. The mechanisms of Hg transport during these events are poorly understood and yet may influence Hg bioavailability and exposure to aquatic biota. Three storm events with varying magnitude and intensity were investigated (June, September and November 2005) at a forested watershed in the Adirondack region of New York State, USA. Concentrations of Hg species increased during thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 42 publications
(94 reference statements)
1
34
0
Order By: Relevance
“…Podzolization, the process of SOM complexing and eluviating Fe and other metals from the E horizon to the Bs horizon (Lundstöm et al, 2000), is likely responsible for the elevated Hg accumulation in the Bs horizon (do Valle et al, 2005; Kaste et al, 2011; Bushey et al, in review ). The accumulation of SOM and Fe oxides in the Bs horizon promote greater Hg accumulation due to increased surface binding sites (Schuster, 1991; Yin et al, 1996; Roulet et al, 1998; Han et al, 2003; Grigal, 2003; Gabriel and Williamson, 2004; Liao et al, 2009; Obrist et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Podzolization, the process of SOM complexing and eluviating Fe and other metals from the E horizon to the Bs horizon (Lundstöm et al, 2000), is likely responsible for the elevated Hg accumulation in the Bs horizon (do Valle et al, 2005; Kaste et al, 2011; Bushey et al, in review ). The accumulation of SOM and Fe oxides in the Bs horizon promote greater Hg accumulation due to increased surface binding sites (Schuster, 1991; Yin et al, 1996; Roulet et al, 1998; Han et al, 2003; Grigal, 2003; Gabriel and Williamson, 2004; Liao et al, 2009; Obrist et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the tributary Hg loads reported herein may be slightly underestimated. An analysis of the response of Hg species to hydrologic events of Archer Creek is available in Bushey et al (2008).…”
Section: Hg Relationship With Doc Somentioning
confidence: 99%
“…Higher K d s suggest a higher affinity of Hg to the particulate phase (Babiarz et al, 1998) and the values observed in the Duluth area streams supported our hypothesis that most of the THg is associated with particles. Bushey et al (2008) while targeting Hg species flux during rainfall events in the Adirondack Mountains, New York, did not find a significant correlation between THg and TSS. However, their two study watersheds were very pristine with TSS val- ues less than 10.5 mg l −1 and they did not analyze spring snow melt runoff events.…”
Section: Resultsmentioning
confidence: 88%
“…Hurley et al (1998) andRolfus et al (2003) estimated that rivers and streams within the Lake Superior basin contributed approximately 33 and 22 percent respectively, of the annual load of mercury to Lake Superior with the majority occurring during spring snowmelt. Many other studies have found elevated concentrations of THg during periods of high flow (Iverfeldt and Johansson, 1988;Scherbatskay et al, 1998;Anderson et al, 2003;Mast et al, 2005;Balogh et al, 2003;Bushey et al, 2008;Schuster et al, 2008;Shanley et al, 2008;Dittman et al, 2010). Sampling during high flow events is crucial primarily because of the high inorganic and organic particulate loads during these periods and the mercury associated with those particles (Balogh, 1997;Mason and Sullivan, 1998;Grigal, 2002;Wall et al, 2005;Dittman et al, 2010).…”
Section: Introductionmentioning
confidence: 94%